Pengaruh Problem Based Learning (PBL) terhadap Kemampuan Berpikir Kritis Siswa MTs: The Influence of Problem Based Learning (PBL) on the Critical Thinking Skills of MTs Students - Nur Khilal Zahra Siregar; Eva Julyanti; Laili Habibah Pasaribu (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
Critical thinking is a high-level thinking skill that is very important in learning mathematics. However, students' critical thinking skills at the Madrasah Tsanawiyah level remain relatively low due to a teacher-centered learning process. Therefore, a learning model that encourages active student involvement in the problem-solving process is needed. This study aims to determine the effect of the Problem-Based Learning (PBL) model on the critical thinking abilities of grade VIII MTs students regarding the topic of probability. This study uses a quantitative, quasi-experimental research design with a pretest-posttest control group. The research sample comprised 67 students: 30 in the experimental class and 37 in the control class. The research instrument was an essay test used to measure students' critical thinking ability. Data analysis was conducted using normality and homogeneity tests, paired-samples t-tests, independent-samples t-tests, and N-Gain calculations to determine increases in students' abilities. The results showed that the application of the Problem-Based Learning (PBL) model had a significant effect on students' critical thinking ability (p=0.000 < 0.05). The average score of students in the experimental class increased from 40.67 in the pretest to 80.83 in the posttest, while the control class showed no significant improvement. The results of the N-Gain calculation showed that the increase in critical thinking skills in the experimental class was in the medium category, with a value of 69.2%, whereas the control class was in the low category, with a value of 0.5%. Thus, the Problem-Based Learning (PBL) model has proven effective at improving students' critical-thinking skills in probability.